Oukoubah: Justice for the Cham Muslims under the Democratic Kampuchea Regime by Ysa Osman (Cambodia: Documentation Center of Cambodia, 2002. 154 pages.) (American Journal of Islam and Society, 2006)
Imagine that a struggling revolutionary movement is promising paradiseafter your defenseless country is unwillingly sucked into the maelstrom oftotal war; that the revolutionary leaders are highly respected men andwomen, many of whom were educated in the former colonial master’shomeland; and that the ruler, who is credited with single-handedly achievingyour nation’s independence and enjoys near-divine status among the masses, joins the revolutionaries after being overthrown and calls upon youto do likewise. And then, full of post-victory idealism, imagine that you livefor three years, eight months, and twenty days in the horror that introduceda new word into the English language: auto-genocide. Welcome to DemocraticKampuchea, whose ruling elite, the Khmer Rouge, targeted theauthor’s people, the Cham Muslims, for extermination: “The enemies ofAngkar [the “Organization”] come in many categories, but the biggest enemiesare the Cham. The plan is to destroy them all before 1980” (p. 6).This book is divided into five parts: “Introduction,” “S-21 PrisonerCases,” “Analysis,” “References,” and “Appendix.” The “Introduction” dealswith the controversial questions of how many Cham died under the KhmerRouge (from 77,000 to 400,000-500,000) and how many lived in Cambodiabefore the Khmer Rouge took over (from about 250,000 to 700,000, the latternumber being accepted by the Cham). Osman then moves on to how theKhmer Rouge sought to destroy community solidarity: turning Cham againstCham and children against parents, forbidding Islamic and Cham customs intoto, destroying the Qur’an and the keitab (a book explaining the Qur’an),making local leaders “disappear,” splitting up families during forced evacuations,and resettling the Cham among ethnic Khmer and Chinese. He alsoexplains why he chose the thirteen case studies that make up the next part:“…there is sufficient documentation for study and research” (p. 8) ...